Identification of a Novel (-)-5-Epieremophilene Synthase from Salvia miltiorrhiza via Transcriptome Mining - Fang, Xin; Li, Chen-Yi; Yang, Yue; Cui, Meng-Ying; Chen, Xiao-Ya; Yang, Lei (Frontiers in Plant Science, 2017)
Salvia miltiorrhiza, a medicinal plant in China, has been used for thousands of years to treat coronary heart diseases. Although biosynthesis of tanshinones, a group of diterpenoids in S. miltiorrhiza, has been extensively investigated, to date we know little about the formation of monoterpenes and sesquiterpenes in this medicinal plant. Here, we report the characterization of three sesquiterpene synthases, named SmSTPS1, SmSTPS2 and SmSTPS3, which catalyzed the formation of a new compound, (-)-5-epieremophilene. Additionally, the (-)-5-epieremophilene biosynthesis activity of SmSTPS1 was confirmed by transient expression in Nicotiana benthamiana. Despite the similar enzyme activities of SmSTPS1, SmSTPS2 and SmSTPS3, the three (-)-5-epieremophilene synthase genes displayed different spatial expression patterns and responded differently to hormone treatments, implicating their specific roles in plant-environment interactions. Our results provide valuable data to understanding the biosynthesis and composition of terpenes in plant.